Efficient H–D Exchange Reactions Using Heterogeneous Platinum-Group Metal on Carbon–H2–D2O System - Sawama, Yoshinari; Monguchi, Yasunari; Sajiki, Hironao (Synlett, 2012)
Deuterium-labeled compounds are widely utilized in various scientific fields. Although the H–D exchange reaction is a straightforward method to produce the deuterated organic compounds, it requires expensive deuterium (D2) gas and/or harsh reaction conditions in conventional methods. This Account summarizes platinum-group metal on carbon (e.g., Pd/C, Pt/C, Ru/C, Rh/C)-catalyzed efficient multi and/or site-selective H–D exchange methods of various compounds including bioactive molecules, such as amino acids, nucleic acids, pharmaceuticals, agrochemicals, and sugars, under neutral and H2-atmospheric conditions in D2O.1 Introduction and Background1.1 H–D Exchange Reaction under Acidic or Basic Conditions1.2 Transition-Metal-Catalyzed H–D Exchange Reaction1.3 H–D Exchange Reaction under Supercritical State or Hydrothermal Conditions1.4 Other H–D Exchange Methods2 Pd/C-Catalyzed H2–D2 Exchange Reaction3 Site-Selective Benzylic Deuteration under Normal Pressure at Room Temperature4 Multi H–D Exchange Reaction under Heat Conditions4.1 Multi H–D Exchange Reaction of Alkyl-Substituted Aromatics4.2 Multi H–D Exchange Reaction of Heterocyclic Compounds4.3 Multi H–D Exchange Reaction of Aromatic Nuclei4.4 Multi H–D Exchange Reaction Using a Mixture of Pd/C and Pt/C or Pd–Pt Hybrid Catalyst5 H–D Exchange Reaction of Simple Alkanes6 H–D Exchange Reaction of Alcohols6.1 The Regioselective H–D Exchange at the α-Position of Aliphatic Alcohols6.2 The Regio- and Stereoselective Deuterium Labeling of Sugars7 Conclusion
Keywords: H–D exchange; D2 gas; heterogeneous catalysis; platinum-group metals; isotope labeling